Development of mE-Book Based Practical Arabic syntax - Luthfi Anisatin; Sunarto Sunarto; Moh. Fery Fauzi (IAIN Salatiga, 2021)
The development of practical Arabic syntax based on mE-Book teaching materials is regarding printed materials that are less effectively applied in online learning. This research and development (RD) aimed at developing practical Arabic syntax teaching materials based on mE-Book for more effective learning without limited space and time using the ADDIE design model. It was carried out through 5 stages: analysis, design, development, implementation, and evaluation. The implementation phase was carried out using a blended learning model. The research results were: 1) the teaching material format is HTML (based flash) published using kvisoft flipbook maker pro 4.2.2.0 software. 2) the teaching material consists of an outside and inside covers, a sample material, a task/question, i'rab, qawaid, a bibliography, and a back cover. 3) the learning video was in the form of a webcam with the help of PowerPoint software and an O-Matic screencast. The results of the assessment were as follow: from material experts was 82% (eligible), from language expert was 100% (very decent), from media expert was 96% (very decent), from students' interest test was 90% (very feasible), from educator response test was 84% (very feasible). The effectiveness test of the large group obtained an average posttest score of 85 and average pretest score of 75. The overall results show that mE-Book practical Arabic syntax is feasible at SMA Surya Buana Malang.